Examining the Effect of Consumer Demographic Characteristics on Online or Offline Shopping Preference - Sisca; Wijaya, Andy; Ernest Grace; Vivi Candra; Novelyn Sidabutar (International Journal of Science, Technology & Management, 2022)
Digitization has become something that is inherent in our daily habits, one of which is shopping habits. In addition to shopping for fashion products by visiting offline stores directly, consumers are also given the opportunity to purchase fashion products online whenever and wherever they are. This study aims to determine the effect of consumer demographic characteristics on their preferences for shopping fashion products offline or online. Data collection is carried out by distributing questionnaires online through whatsapp and telegram groups during June-July 2021, which resulted in 162 responses. Chi-Square and Kruskal-Wallis tests are used to test the hypothesis. The results prove that there are insignificant results between consumer demographic characteristics and preferred shopping method. Furthermore, research data also shows that more than half of the respondents still prefer to shop for fashion products offline rather than online although in the Covid-19 pandemic situation because they want to evaluate the product physically.